Combined gravity and magnetic studies of satellite bodies associated with the giant Coompana negative magnetic anomaly in South Australia. Issue 1 (1st December 2018) - Foss, Clive; Heath, Philip; Wise, Tom; Dutch, Rian
Abstract : We present inversion models derived for 3 gravity and magnetic anomaly pairs. These anomalies are associated with the much larger (>50 km diameter) Coompana negative magnetic anomaly, and are due to high density and strong, reverse remanent magnetization. Recent drilling has revealed gabbroic rocks are likely to be the principal causes of these anomalies. In some cases the gravity and magnetic anomaly models are quite similar to each other, and from these we mostly gain estimates of the magnetization to density relationships. In particular, these cases confirm that the magnetization direction estimates derived from inversion of the magnetic field data are robust. In other cases the gravity and magnetic inversion models differ significantly, revealing that the simple models derived from inversion of either dataset alone do not well represent what is clearly a more complex geology. The main advantage from the combined gravity and magnetic data is to compare the information each separately provides. We hope to upgrade our inversion models with physical property values measured on core recovered from the recently drilling campaign. At that time, and in conjunction with petrological studies, we should be able to introduce more geological interpretation and guidance to modify and transform the initial inversion results which are primarily geophysical to models that are more geological.